Length-weight relationships for the fifty littoral and coastal marine fish species from the Eastern Adriatic Sea - Soldo, Alen (2020)
The length–weight relationship parameters are reported for the fifty littoral and coastal marine fish species from the Eastern Adriatic. Captures were made between the years 2004 and 2017 during sport fishing competitions. The parameters a and b of the equation W = aLb were estimated. The b values ranged from 2.1972 for Spicara smaris (Linnaeus, 1758) to 3.7044 for Salaria pavo (Risso, 1810). The L-W relation for Scyliorhinus stellaris (Linnaeus, 1758), Gobius bucchichi Steindachner 1870, Gobius geniporus Valenciennes 1837 and Lipophrys trigloides (Valenciennes, 1836) are not available in FishBase and presents new data for these species. For some other species, such as Labrus mixtus Linnaeus 1758, there are only two relationships, but none from the Mediterranean, for Gobius paganellus Linnaeus 1758 only four relationships and none from Central and Eastern Mediterranean, while for Labrus merula Linnaeus 1758, Symphodus mediterraneus (Linnaeus, 1758), Symphodus roissali (Risso, 1810), Gobius cobitis Pallas 1814, Gobius cruentatus Gmelin 1789, Gobius niger Linnaeus 1758, Parablennius gatorugine (Linnaeus, 1758), Parablennius sanguinolentus (Pallas, 1814), Salaria pavo (Risso, 1810), and Bothus podas (Delaroche, 1809) very low number of relationships are presented and none from the Adriatic Sea.
Parametri dužinsko-masenog odnosa su prijavljeni za 50 litoralnih i obalnih rba iz istočnog Jadrana. Svi primjerci su ulovljeni u periodu 2004-2017 za vrijeme natjecanja u sportskom ribolovu. Parameteri a i b od jednadžbe W = aLb su prezentirani. Vrijednosti b parametra su varirale od2.1972za Spicara smaris (Linnaeus, 1758) do3.7044 za Salaria pavo (Risso, 1810). Dužinsko-maseni odnosi za Scyliorhinus stellaris (Linnaeus, 1758), Gobius bucchichi Steindachner 1870, Gobius geniporus Valenciennes 1837 i Lipophrys trigloides (Valenciennes, 1836) dosad nisu bili dostupni u FishBase. Za neke druge vrste, primjerice Labrus mixtus Linnaeus 1758, postoje samo dva prijavljena odnosa, pri čemu niti jedan nije iz Mediterana, za Gobius paganellus Linnaeus 1758 postoje samo 4 odnosa i nijedan iz središnjeg i istočnog Mediterana, dok za Labrus merula Linnaeus 1758, Sym-phodus mediterraneus (Linnaeus, 1758), Symphodus roissali (Risso, 1810), Gobius cobitis Pallas 1814, Gobius cruentatus Gmelin 1789, Gobius niger Linnaeus 1758, Parablennius gatorugine (Linnaeus, 1758), Parablennius sanguinolentus (Pallas, 1814), Salaria pavo (Risso, 1810) i Bothus podas (Delaroche, 1809) postoji veoma mali broj dužinsko-masenih odnosa, pri čemu niti jedan nije prijavljen za Jadransko more, osim za T. radiates.
Bibliografija: str. 209-210.
Summary ; Sažetak.
Keywords: Morske ribe -- Dužinsko-maseni odnos -- Primorje -- Priobalje; Jadransko more